Valdemar's Abjection: Poe, Kristeva, Masculinity, and Victim-Monsters. Issue 3 (3rd July 2018) - Greven, David
ABSTRACT: This article explores intersections between Edgar Allan Poe's 1845 tale "The Facts in the Case of M. Valdemar" and Julia Kristeva's Powers of Horror: An Essay on Abjection (1982). Highly influential, Kristeva's work illuminates Poe's depiction of a man mesmerized on the point of death, his vibrating tongue the only indication of life. In his liminal condition between life and death, Valdemar transforms into a spectacle witnessed over time by a male group whose members remain intimately tied to yet always distant and aloof from him. As a spectacle of body horror, Valdemar evokes many of the attributes of Kristevan abjection theory, especially the fluids and waste materials associated with the maternal body. Challenging the maternal focus of abjection theory and its reception, I track the ways in which Poe's tale locates abject affect in the fears of the male body and in the male group's relationship to the expulsed, isolate male. Another antebellum author, the health reformer Sylvester Graham, provides a striking point of comparison in his focus on the young male onanist. Through Kristeva's and Poe's works, I develop a theory of the victim-monster, a being whose suffering initially incites sympathy but ultimately repels the spectator; the victim becomes monstrous, his or her suffering the true site of a horror that must be transcended to ensure the survival of the spectator. The victim-monster of Poe's tale intersects with the figure of the grotesque and anti-Semitic caricature.